Strategi Reformasi Hukum Administrasi Negara dalam Peningkatan Kinerja Pelayanan Publik di Era Digital - Refania Varetta Sugiarto (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Reforming administrative law is a crucial step in improving the performance of public services, especially in the increasingly developing digital age. The background of this research is the need for updates in the bureaucratic and regulatory system to meet the demands for faster, more efficient, and transparent services. The problem addressed is how administrative law reform strategies can improve the quality of public services in the digital age. The research method used is a descriptive approach with qualitative analysis. The research results indicate that administrative law reform driven by technology can improve bureaucratic efficiency, speed up service processes, and minimize the potential for abuse of power. This research concludes that the implementation of digitalization and appropriate regulations can improve the performance of public services. The advice given is the importance of collaboration between the government and the community in implementing reforms.